Issues Related to rape – A study and an Investigation - Khudair, Najm; Khalaf , Fahd (Islamic Sciences Journal, 2023)
ABSTRACT After studying and researching the matter, it became clear to us that rape is two-fold: what sin is not related to. The second: What is a sin related to. Any one who uses an animal other than his own without permission, he is a guarantor, except in some cases. Likewise, the fatwa guaranteeing the endowment. Likewise, whoever behaves with another slave and the slave perished will be a guarantor in this case, as well as whoever rape something, he guarantees it if he is homosexual, Sheikhs have spoken about knowing the decrease. And the separated as well as the connected increases of the violated person, are not guaranteed, except by damage or prevension Also, there is no need to guarantee anything without stinginess according to Abu Hanifa - may God rest his soul - And Ahmad, and he gives up the benefits of preparing for exploitation, endowment, orphan's money by guarantee, and others assuredly.